The Iberian Massif Landscape and Fluvial Network in Portugal: a geoheritage inventory based on the scientific value - Pereira, D. I. (2015)
Integrated in the national inventory of geological heritage in Portugal, the “Iberian Massif Landscape and Fluvial Network” was selected as one of the geological frameworks with international relevance. Taking into account the diversity of geomorphological and stratigraphic elements occurring in the Portuguese Iberian Massif, 38 geosites were selected in order to represent five themes related to the main geomorphological elements of the Iberian Massif Landscape: major residual landforms, granite landforms, tectonic landforms, correlative sediments, and fluvial landforms. For each theme, some sub-themes were defined, together with key-areas that were considered for the selection of geosites. A quantitative assessment of the scientific value and vulnerability of all geosites was undertaken using a methodology that numerically scores a set of criteria. Results highlight the Vilariça geosite with top-priority for management based on its high scientific value and high vulnerability, and the key-area of Miranda do Corvo-Lousã Basin because of the high concentration of geosites. The quantitative evaluation shows that seven geosites have high vulnerability and that special attention should be paid to sedimentary sections. These results allow the establishment of priorities for the management of geosites under the scope of a national geoconservation strategy.